Current surgical treatment options for ocular complications of Stevens-Johnson and Lyell's syndromes - V.F. Chernysh; N.N. Haritonova; A.N. Kulikov; P.A. Kacherovich; A.A. Kol'bin (РМЖ "Клиническая офтальмология")
V.F. Chernysh, N.N. Haritonova, A.N. Kulikov, P.A. Kacherovich, A.A. Kol'bin S.M. Kirov Military Medical Academy, St. Petersburg, Russian Federation Epidermolytic drug reactions (EDR) are severe acute drug-induced allergic disorders characterized by extensive lesions of the skin and mucous membranes. Drug-induced Stevens-Johnson and Lyell's syndromes manifested with acute skin and mucous membrane disorders and often leading to lethal outcome may affect eyelids and ocular surface with different levels of severity and thus can cause serious functional ocular complications. The authors present two clinical reports of patients with ocular EDR manifestations in acute and long-term time periods and review the currently available effective treatment options for patients with such ocular complications and their consequences. The article describes surgical treatments which enabled to achieve satisfactory anatomical and functional results in patients with the above disorders. Timely treatment of Stevens-Johnson and Lyell's syndromes comprising systemic and topical conservative therapy in combination with surgical procedures during the acute stage plays an important role for the prediction of severe long-term ocular complications. The elimination of ocular complications caused by these syndromes is associated with multistage reconstructive surgery. The authors emphasize that long-term follow-up by ophthalmologist will be required for patients who survived Stevens-Johnson and Lyell's syndromes. Keywords: epidermolytic drug reactions, Stevens–Johnson syndrome, Lyell's syndrome, amniotic membrane transplantation, dry eye syndrome, pseudomembranous blepharoconjunctivitis, multistage reconstructive surgery. For citation: Chernysh V.F., Haritonova N.N., Kulikov A.N. et al. Current surgical treatment options for ocular complications of Stevens-Johnson and Lyell's syndromes. Russian Journal of Clinical Ophthalmology. 2023;23(2):99–106 (in Russ.). DOI: 10.32364/2311-7729-2023-23-2-99-106.